Electrochemical evaluation of silver - fullerenes nanocomposites as catalysts for electrodes in flexible zinc - air batteries - Chipoco Haro, Danae Ariana (2020)
Metal-air batteries are characterized by a high energy density with relatively simple and safe chemistry which makes them suitable for many applications, especially the ones requiring flexibility. These energy storage devices consist of one metal electrode, an air electrode, which enhance the oxygen evolution and oxygen reduction reactions (OER and ORR, respectively), and an electrolyte. The air electrode is lighter than most metal electrodes present in batteries; therefore, these batteries have a high energy density. However, the most critical problem this technology faces involves the air electrode design, especially because of the requirement of a bifunctional catalyst for both OER and ORR. Here, the enhancement of the catalytic activity of silver nanoparticles impregnated on carbon nanotubes (CNT) for OER and ORR using polyhydroxy fullerene (PHF) is discussed, as well as the methodology needed for an experimental demonstration of this hypothesis. The electrochemical tests demonstrated that silver nanoparticles from 60 nm to 70 nm were successfully impregnated over the CNT buckypapers and the electrode was stable over several cycles. The nanocomposite Ag-PHF was also successfully impregnated, but the electrode was not as stable as the electrode with only Ag nanoparticles. However, the higher current achieved by the Ag-PHF electrode confirmed the hypothesis that the presence of PHF enhances the catalytic activity of silver nanoparticles. The implications of our findings in the improvement of materials for Zn-air batteries is discussed. This study contributes to the worldwide efforts of the scientific community to develop flexible, small and light batteries and may be a starting point in the use of PHF for this application.